MARKETING POLICIES THROUGH THE INTERNET: THE CASE OF SKIING CENTERS IN GREECE - Panagiotis LEFAKIS; Christos BATZIOS; Theodoros KOUTROUMANIDIS; Zacharoula ANDREOPOULOU; Christiana KOLIOUSKA; Georgios TSEKOUROPOULOS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Lately, Internet constitutes a major tool for transactions in every aspect and supports innovative marketing policies. Broadband Internet has become “the key to success” for businesses, as it offers various advantages and benefits through Internet marketing (e-marketing) policies. In Greece, mountainous areas are usually covered with snow during winter months; so, skiing centers have become an important asset for winter tourism. The Internet evolution and the development of network infrastructure enhance marketing policies for winter tourism activities. This paper studies the use of marketing policies in Greek skiing centers through the Internet, such as promotional activities, website interactivity, accommodation & entertainment information, online weather forecast, guest book, etc Therefore, the paper aims to optimize and evaluate skiing centers in Greece, qualitatively and quantitatively according to e-marketing policies used as criteria, based on the multicriteria method of PROMETHEE II and further to classify them in groups. Finally we identify and describe the optimum group of skiing centers to be used as a model with enhanced customer communication services.